2021
DOI: 10.1021/acsami.1c03201
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Molecular Network Built from Hierarchy Self-Assembly of Perylene Bisimide Derivatives

Abstract: The structures of two-dimensional (2D) self-assembled molecular networks formed by a series of perylene bisimide (PBI) derivatives were investigated by scanning tunneling microscopy (STM). By introducing different functional groups to the PBI rings, we successfully built a different self-assembled molecular network on the liquid−solid interface. When the substituent is propanol, PBI is aligned in lines. When we introduced either an ester group or an amide group to the PBI compounds, they tended to form dimers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Due to its potential application toward advanced functional materials, diverse self-assembly on the substrate has been an area that received immense attention. Solvent and concentration are two factors that function well in controlling the packing mode of molecules in the monolayer. In this present work, if we compare the self-assembly of TTF in 1-OA, 1-PO, and n -TD, at the same concentration of 1.5 × 10 –4 M, the molecules are packed into alternate-III, linear-II, and linear-III structures. In the same solvent and variable concentrations, for example, in 1-OA, as the concentration decreases, the disordered phase, alternate-I, alternate-II, alternate-III, linear-I, and S-like structures appear subsequently.…”
Section: Resultsmentioning
confidence: 87%
“…Due to its potential application toward advanced functional materials, diverse self-assembly on the substrate has been an area that received immense attention. Solvent and concentration are two factors that function well in controlling the packing mode of molecules in the monolayer. In this present work, if we compare the self-assembly of TTF in 1-OA, 1-PO, and n -TD, at the same concentration of 1.5 × 10 –4 M, the molecules are packed into alternate-III, linear-II, and linear-III structures. In the same solvent and variable concentrations, for example, in 1-OA, as the concentration decreases, the disordered phase, alternate-I, alternate-II, alternate-III, linear-I, and S-like structures appear subsequently.…”
Section: Resultsmentioning
confidence: 87%
“…syn-6: 1 H NMR (500 MHz, CDCl 3 ) d 7.64 (s, 3H), 6.85 (s, 3H), 4.18 (dd, J ¼ 9.7 and 13.2 Hz, 3H), 2.77 (dd, J ¼ 4.9 and 13.5 Hz, 3H), 2.12 (s, 9H), 1.87-1.79 (m, 3H), 1.14 (d, J ¼ 6.6 Hz, 9H), 0.93 (d, J ¼ 6.6 Hz, 9H); 13 4.39 (dd, J ¼ 9.5 and 13.2 Hz, 1H), 4.05 (dd, J ¼ 8.7 and 13.3 Hz, 1H), 3.68 (dd, J ¼ 7.9 and 13.3 Hz, 1H), 3.45 (dd, J ¼ 6.9 and 13.5 Hz, 1H), 3.08 (dd, J ¼ 6.0 and 13.2 Hz, 1H), 2.79 (dd, J ¼ 5.3 and 13.3 Hz, 1H), 2.36 (s, 3H), 2.26 (s, 3H), 1.98 (s, 3H), 1.95-1.79 (m, 3H), 1.07-1.04 (m, 6H), 1.02 (d, J ¼ 6.6 Hz, 3H), 1.00-0.98 (m, 6H), 0.93 (d, J ¼ 6.9 Hz, 3H); 13 1, entry 8). To a mixture of syn-6 (50.0 mg, 0.0622 mmol), Pd(t-Bu 3 P) 2 (5.0 mg, 0.0098 mmol), and KOAc (25.6 mg, 0.261 mmol), dry DMA (1.8 mL) was added under an argon atmosphere.…”
Section: General Experimental Methodsmentioning
confidence: 99%
“…1 The size of coronene is suitable for processing techniques. Several applications have been investigated, including building blocks for self-assembling compounds 2–4 and organic transistors. 5–8 Doping of heteroatoms in aromatic rings is an effective approach for modulating physico-electrochemical properties, and several synthetic studies of heterocoronenes have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…19 Most of the previous work did not study the hydrogen bonds of the substituent on the PDIs, particularly, at the bay positions. Recently, our group 20 investigated the differences of 2D self-assemblies between the absence and presence of the hydrogen bonds at the imide positions. The PDI derivatives with highly directional hydrogen bonds formed a hexagon network, which was favorable to construct host–guest networks.…”
Section: Introductionmentioning
confidence: 99%